2018
DOI: 10.1002/ajmg.a.38829
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in Rett syndrome: Impact and management including use of sleep hygiene practices

Abstract: Sleep disturbances are debilitating for individuals with Rett syndrome (RTT) and their families yet the evidence base for management is poor. We investigated management strategies and their relationships with sleep problems. Data were provided by 364/461 (79%) families with a child with RTT and registered with the International RTT Phenotype Database. Logistic regression models were used to investigate relationships between impacts of sleep problems on the child and family with age group, mutation type, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…23 The majority of cross-sectional studies (5 articles) also involved data collection through in person assessments; 2 studies that were multisite 24 25 and 3 that were single institution. [26][27][28] Of the remaining cross-sectional studies (4 articles), three involved data collection through remotely disseminated caregiver completed questionnaires [29][30][31] and a single study involved retrospective medical records review. 32 The multisystem nature of the disorder is quite apparent based on the observational studies identified in this scoping review (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…23 The majority of cross-sectional studies (5 articles) also involved data collection through in person assessments; 2 studies that were multisite 24 25 and 3 that were single institution. [26][27][28] Of the remaining cross-sectional studies (4 articles), three involved data collection through remotely disseminated caregiver completed questionnaires [29][30][31] and a single study involved retrospective medical records review. 32 The multisystem nature of the disorder is quite apparent based on the observational studies identified in this scoping review (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Even though sleep medications may have reduced sleep problems, many individuals using medications to aid sleep, especially combination therapy, remain likely to have more difficulty initiating and maintaining sleep as well as greater impacts from sleep problems. 7 This could be due to a reverse relationship as those requiring sleep medication generally sleep worse than those who are not on any medication. In regard to treatment approaches, this study shows that parents consider a "bedtime routine," familiar environment, and a regular daytime routine critical for good sleep quality.…”
Section: Medicationmentioning
confidence: 99%
“…4 A study by Boban et al also demonstrated that sleep hygiene strategies such as following a bedtime routine, going to bed at the same time each night, and having a dark room were frequently used by RTT patients to aid good sleep. 7 Nevertheless, drug trials need to be designed that further investigate the long-term efficacy and safety of melatonin and retarded melatonin being used as a hypnotic agent RTT patients. The heterogeneity of RTT and the unsatisfactory outcome measures limit the implementation and success of drug trials.…”
Section: Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep dysfunction is a prominent co-morbidity reported in 80% of patients with RTT [92,93,94], and sleep deprivation has been investigated as an aggravating factor in epilepsy [95]. Low sleep efficiency, long sleep-onset latency, and a short and fragmented total sleep time have been reported in RTT [94].…”
Section: Introductionmentioning
confidence: 99%